Accuracy of Self-Reported Physical Activity Levels in Obese Adolescents. (26th August 2014) - Elliott, Sarah A.; Baxter, Kimberley A.; Davies, Peter S. W.; Truby, Helen
Abstract : Introduction. Self-reported measures of habitual physical activity rely completely on the respondent's ability to provide accurate information on their own physical activity behaviours. Our aim was to investigate if obese adolescents could accurately report their physical activity levels (PAL) using self-reported diaries. Methods. Total energy expenditure (TEE) was measured using doubly labelled water (DLW) and resting energy expenditure (REE) was measured via indirect calorimetry. Activity energy expenditure (AEE) and PAL values were derived from measured TEE and REE. Self-reported, four-day activity diaries were used to calculate daily MET values and averaged to give an estimated PAL value (ePAL). Results. Twenty-two obese adolescents, mean age13.2 ± 1.8 years, mean BMI31.3 ± 4.6  kg/m 2, completed the study. No significant differences between mean measured and estimated PAL values were observed (1.37 ± 0.13 versus1.40 ± 0.34, P = 0.74 ). Bland Altman analysis illustrated a significant relationship (r = - 0 . 76, P < 0.05 ) between the two methods; thus the bias was not consistent across a range of physical activity levels, with the more inactive overreporting their physical activity. Conclusion. At an individual level, obese adolescents are unlikely to be able to provide an accurate estimation of their own activity.